Technique for Identification of Electrical Substation Equipment Through Auto-Framing Interest Points and OCR Recognition of Text Tags in Environment for Augmented Reality Systems - Ferreira, Angel Rodrigues; Pereira Neto, Jair de Oliveira; Cardoso, Alexandre; Lamounier Junior, Edgard; Aureliano Júnior, Maurício José; de Lima, Diogo Cavalcante; Silva, Alexandre Carvalho; Campos, Davidson Pereira; Feitosa, João Batista Soares (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Electrical power substation systems are considered critical environments with a high impact factor on society. Although Augmented Reality (AR) solutions are becoming increasingly prevalent in the future of Industry 4.0, there is a concern about the practicality of using these systems. AR has significant potential to support assisted maintenance of substation components by projecting field asset information onto an AR headset. To enhance this process, a technique was proposed to identify equipment by automatically reading text from its tags using OCR (generally manual) and using auto-framing through object detection (with Neural Networks). The developed solution can be tested and evaluated in a laboratory setting. The conditions evaluated when pointing a camera at the image of the equipment's operation box with his text identification tag showed that the method employed by the technique can achieve relatively better results than manual framing, making the equipment identification process efficient and potentially promising for implementation in AR devices.